2018
DOI: 10.1007/s10461-018-2100-y
|View full text |Cite
|
Sign up to set email alerts
|

Syndemic Conditions, HIV Transmission Risk Behavior, and Transactional Sex Among Transgender Women

Abstract: This study examined the effect of four syndemic conditions-namely, polydrug use, depression, childhood sexual abuse, and intimate partner violence-on rates of HIV transmission risk behavior (TRB) and separately, transactional sex among transgender women. TRB was defined as the number of condomless penetrative sex events with a casual or main partner of discordant or unknown HIV status. Using data from 212 transgender women in New York City, multivariable analyses revealed that, compared to those with no syndem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 56 publications
(92 reference statements)
0
40
2
1
Order By: Relevance
“…Having transactional partners was also frequently reported (71%) and, in this case, none of the psychosocial conditions was related to this behavior. Our findings contrast with those of other studies in transgender women from North America, India, and Jamaica 19 , 35 , 40 relating the accumulation of psychosocial adversities to greater HIV risk behaviors.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Having transactional partners was also frequently reported (71%) and, in this case, none of the psychosocial conditions was related to this behavior. Our findings contrast with those of other studies in transgender women from North America, India, and Jamaica 19 , 35 , 40 relating the accumulation of psychosocial adversities to greater HIV risk behaviors.…”
Section: Resultscontrasting
confidence: 99%
“…In our sample of transgender women, 62% engaged in unprotected sex, a figure consistent with another report in a larger Colombian sample 38 . Childhood sexual abuse, illicit drug use, and alcohol misuse were reported frequently by transgender women, factors that have been related to greater HIV risk behaviors in transgender women elsewhere 19 , 39 . We found only one factor, forced sex, to be related to unprotected sex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgender women, although resourceful and resilient, are a highly vulnerable and marginalized population in the United States (US) as well as globally, experiencing high rates of stigma, discrimination, and violence (1)(2)(3)(4)(5). Consequently, given the association of negative health outcomes with stigma and discrimination, transgender women experience severe health disparities across a number of outcomes, including HIV (6)(7)(8)(9). Although no national data yet exist in the US, a meta-analysis found that 28% of transgender women tested positive for HIV (7).…”
Section: Introductionmentioning
confidence: 99%
“…8 However for trans women and gender diverse groups there continues to be disempowerment, with syndemics of drug use, intimate partner violence, mental ill-health and transactional sex driving HIV and other STI acquisition: considerable stigma, discrimination, marginalisation and persecution remain. 9 In MSM and trans women who do not inject drugs, HIV transmission is predominantly transmitted via penetrative penile-anal sex 10,11 Design and delivery of effective interventions for the prevention of HIV have focussed on penetrative penile-anal sexual behaviours. A combination of effective HIV treatment, HIV treatment as prevention, a significant increase in HIV testing, access to HIV pre-exposure prophylaxis and vaccines against STIs as well as interventions improving condom use have significantly reduced the incidence of HIV in some populations of MSM.…”
mentioning
confidence: 99%